Wykorzystanie ścieżki proporcjonalnego rozwoju w badaniach społecznych - Strahl, Danuta (Wydział Prawa i Administracji UAM, 1982)
The article is an attempt of application of proportional development path structure to social studies. The author describes the path structure on the basis of social infrastructure distinguishing its three subsystems, i.e. health service, education and culture. The construction of proportional development path is accomplished in two stages. The first stage encompasses indication of such individual development pattern for 49 voivodships of Poland which leads to reaching internal equilibrium by each of the three subsystems. The second stage leads to the study objects equilibrium in a scope of integrated system of social infrastructure.
Application of Proportional Developement Path in Social Studies